Supraglottoplasty for laryngomalacia with obstructive sleep apnea: A systematic review and meta-analysis - Camacho, M (2016)
OBJECTIVES/HYPOTHESIS: To determine if apnea-hypopnea index (AHI) and lowest oxygen saturation (LSAT) improve following isolated supraglottoplasty for laryngomalacia with obstructive sleep apnea (OSA) in children. STUDY DESIGN: Systematic review and meta-analysis. METHODS: Nine databases, including PubMed/MEDLINE, were searched through September 30, 2015. RESULTS: A total of 517 studies were screened; 57 were reviewed; and 13 met criteria. One hundred thirty-eight patients were included (age range: 1 month-12.6 years). Sixty-four patients had sleep exclusive laryngomalacia, and in these patients: 1) AHI decreased from a mean (M) ± standard deviation (SD) of 14.0 ± 16.5 (95% confidence interval [CI] 10.0, 18.0) to 3.3 ± 4.0 (95% CI 2.4, 4.4) events/hour (relative reduction: 76.4% [95% CI 53.6, 106.4]); 2) LSAT improved from a M ± SD of 84.8 ± 8.4% (95% CI 82.8, 86.8) to 87.6 ± 4.4% (95% CI 86.6, 88.8); 3) standardized mean differences (SMD) demonstrated a small effect for LSAT and a large effect for AHI; and 4) cure (AHI < 1 event/hour) was 10.5% (19 patients with individual data). Seventy-four patients had congenital laryngomalacia, and in these patients: 1) AHI decreased from a M ± SD of 20.4 ± 23.9 (95% CI 12.8, 28.0) to 4.0 ± 4.5 (95% CI 2.6, 5.4) events/hour (relative reduction: 80.4% [95% CI 46.6, 107.4]); 2) LSAT improved from a M ± SD of 74.5 ± 11.9% (95% CI 70.9, 78.1) to 88.4 ± 6.6% (95% CI 86.4, 90.4); 3) SMD demonstrated a large effect for both AHI and LSAT; and 4) cure was 26.5% (38 patients with individual data). CONCLUSION: Supraglottoplasty has improved AHI and LSAT in children with OSA and either sleep exclusive laryngomalacia or congenital laryngomalacia; however, the majority of them are not cured.